Temperature impact upon structural and thermal physical properties of epoxy composites modified with 4,4-sulfonil bis (4,1-phenylene) bis (n,n-diethyldithiocarbamate) - D.A. Zinchenko, A.V. Buketov, S.A. Smetankin (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
The effect of the 4.4-sulfonilbis (4,1-phenylene) bis (n,n-diethyldithiocarbamate) (C22H28N2O2S5) modifier on the thermal properties of the epoxy bisphenol oligomer ED-20 within the temperature range ΔT = 303–873 K has been defined. The heat resistance by Martens, thermal expansion coefficient, glass transition temperature and shrinkage have been studied. As the result of the acquired data analysis, the optimum concentration of the C22H28N2O2S5 modifier, significantly improving the thermal properties of epoxy composite, has been set. It has been demonstrated that in order to get a composite material (CM) or a protective coating with enhanced thermal properties, it is necessary to introduce the optimum amount of modifier into the epoxy binder (q = 0.10–0.25 mass parts out of 100 % ED-20 resin). In this case, the composite is formed with the heat resistance value by Martens of T = 362 K. On the basis of experimental studies of thermal properties using modern research methods such as differential thermal analysis (DTA) and thermogravimetric analysis (TGA) the allowable temperature limits at which it is possible to use modified epoxy composites have been set. СM with the entered modifier of q = 0.75 mass parts and T0 = 601.8 K is characterized by the biggest destruction temperature value if compared with the matrix (T0 = 600.1 K). The difference between the minimum and the maximum value is only ΔT0 = 1.7 K, which indicates insignificant positive impact of modifier upon the initial destruction temperature. Using DTA curves exothermic effects when exposed to the thermal field within the temperature range of CM ΔT = 591.3– 683.7 K have been defined. It has been found out that the maximum values of exothermic peak, if compared with the matrix (Tmax = 618.3 K) are Tmax = 626.6–641.0 K, and they are characteristic for СM, filled with the C22H28N2O2S5 modifier in an amount of q = 0.50–0.75 mass parts. The difference between the minimum (matrix component) and the maximum value is ΔTmax = 22.7 K, which (within experimental error) shows a significant positive impact of the modifier upon the maximum exoeffect value. It is said to increase the thermal stability of CM, which in its turn, is due to the stability of physical and chemical bonds in the material, providing improved physical and mechanical properties of materials under the impact of rising temperatures.